HUBUNGAN ANTARA ASUPAN PROTEIN, ZAT BESI, VITAMIN C, DAN INHIBITOR ABSORPSI ZAT BESI DENGAN STATUS ANEMIA PADA LANJUT USIA DI PAGUYUBAN “WIRA WREDHA” WIROGUNAN, YOGYAKARTA - Allia Khairunnisa; I Dewa Putu Pramantara; Weni Kurdanti (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2017)
The prevalence of anemia in older people based on data from NHANES III by 11,0% of men and 10,2% of women suffered from anemia. The study used observational study with cross sectional design. Subjects for the study were 99 older people at Paguyuban “Wira Wredha” Wirogunan, Yogyakarta who complied for inclusion and exclusion criteria. Data collected include protein intake, iron intake, vitamin C intake, iron absorption inhibitors intake, body weight, and hemoglobin concentration. Data related to intake of protein, iron, vitamin C, and iron absorption inhibitors obtained by interview using SQFFQ. Body weight measured using weight scales. Hemoglobin concentration measured using hemocue method. The statistical test used to analyze the relationship is a Chi Square test or Fisher’s exact test. The prevalence of anemia in older people was 18,2%. There was significant relationship between intake of protein (p=0,005) and iron (p=0,007) with anemia status in older people. There was no significant relationship between intake of vitamin C (p=0,636), iron absorption inhibitors (tannin, phytate, oxalate acid) with anemia status in older people (p=0,184; p=0,129; p=0,393) with anemia status in older people. There were significant relationship between intake of protein and iron with anemia status in older people at Paguyuban “Wira Wredha” Wirogunan, Yogyakarta. There were no significant relationship between intake of vitamin C and iron absorption inhibitors with anemia status in older people at Paguyuban “Wira Wredha” Wirogunan, Yogyakarta. Keywords: Anemia status, iron, iron absorption inhibitors, protein, vitamin C